Conference – 1992 Equation

1 t = 1 ( 1 α ) ln ( α A ) + 1 ( 1 α ) ( p t t 1 w t a ) + u t MathType@MTEF@5@5@+= feaagKart1ev2aaatCvAUfeBSjuyZL2yd9gzLbvyNv2CaerbuLwBLn hiov2DGi1BTfMBaeXatLxBI9gBaerbd9wDYLwzYbItLDharqqtubsr 4rNCHbGeaGqiVu0Je9sqqrpepC0xbbL8F4rqqrFfpeea0xe9Lq=Jc9 vqaqpepm0xbba9pwe9Q8fs0=yqaqpepae9pg0FirpepeKkFr0xfr=x fr=xb9adbaqaaeGaciGaaiaabeqaamaabaabaaGcbaGaaGymamaaBa aaleaacaqG0baabeaakiabg2da9maalaaabaGaaGymaaqaamaabmaa baGaaGymaiabgkHiTiabeg7aHbGaayjkaiaawMcaaaaacaqGSbGaae OBamaabmaabaGaeqySdeMaaeyqaaGaayjkaiaawMcaaiabgUcaRmaa laaabaGaaGymaaqaamaabmaabaGaaGymaiabgkHiTiabeg7aHbGaay jkaiaawMcaaaaadaqadaqaaiaabchadaWgaaWcbaGaaeiDaaqabaGc cqGHsisldaWgaaWcbaGaaeiDaiabgkHiTiaaigdaaeqaaOGaae4Dam aaDaaaleaacaqG0baabaGaaeyyaaaaaOGaayjkaiaawMcaaiabgUca RiaabwhadaWgaaWcbaGaaeiDaaqabaaaaa@583C@